Evaluating the field efficacy of microbial products – important technical matters to consider - O'Callaghan, Maureen; Mansfield, Sarah (New Zealand Plant Protection, 2026)
• Thorough field evaluation of local and imported microbial products under New Zealand growing conditions is needed to ensure growers can use these products with confidence. • There are no uniform guidelines for evaluation of the diverse range and functions of microbial products containing live microorganisms, and trials must be designed to accommodate complex interactions among microorganisms, target pest and crop. • Successful trial outcomes rely on: thorough assessment of prior knowledge of the target and microorganism; detailed pre-trial planning to minimise risk and ensure optimal trial design; well documented trial establishment and monitoring; appropriate statistical analysis of the data; and evaluation of trial outcomes.